Stochastic Modeling of a Measles Outbreak in Brazil - Lau, M.; Arenas, Z. G. (Trends in Computational and Applied Mathematics, 2023)
Development of mathematical models and its numerical implementations are essential tools in epidemiological modeling. Susceptible-Infected-Recovered (SIR) compartmental model, proposed by Kermack and McKendrick, in 1927, is a widely used deterministic model which serves as a basis for more involved mathematical models. In this work, we consider two stochastic versions of the SIR model for analysing a measles outbreak in Ilha Grande, Rio de Janeiro, in 1976; Continuous Time Markov Chain and Stochastic Differential Equations.  The SIR Continuous Time Markov Chain model is used to extract specific information from the measles outbreak, obtaining results in excellent agreement with the reported epidemic values. Numerical simulations are performed in Python.